Hubungan asfiksia dengan kejang pada neonatus di ruang perinatologi dan NICU RSUD Wangaya kota Denpasar - Ruby Kurniawan; I Wayan Bikin Suryawan; Made Ratna Dewi (DiscoverSys Inc., 2019)
Background: Asphyxia is a serious problem in newborns because it can cause high levels of mortality and mortality. Deaths because of asphyxia are around 38% and are 3rd rank in neonatal deaths. Asphyxia is the most common cause of seizures in newborns with the incidence of 1-3 per 1,000 births. Seizure after asphyxia can occur impaired cognitive and developmental disorders in children. From the relationship, well and proper management of infants with asphyxia can reduce the risk of death and permanent disability due to seizures.Methods: Observational analytic research with cross sectional study design to find out the relationship between asphyxia and seizure in neonates. The sample of this study is 718 neonates from 0 to 28 days with asphyxia in perinatology and NICU of Wangaya General Hospital Denpasar city from July 2017-July 2018.Result: The prevalence of neonates with asphyxia are 214 and neonates with seizure are 8 from 214. From this study found a relationship between asphyxia and occurrence of seizure with p=0,000.Conclusion: There is a significant relationship between asphyxia and the occurrence of seizures in neonates.